Moisture buffering potential of plasters for energy efficiency in modern buildings - Fořt, Jan; Doleželová, Magdaléna; Černý, Robert (International Conference “Environmental Engineering”, 2017)
Moisture level significantly affects durability of constructions, their thermal performance and quality of indoor air. Since building envelopes are subjected to a moisture gradient, additional ventilation systems are employed to maintain relative humidity on the desired level. Although modern advanced ventilation systems provide sufficient air exchange rate, their wider application is in conflict with sustainability development principles due to high energy demands. Moreover, according to the European legislation related to the Nearly Zero Energy Buildings (European Directives 2002/91/EC and 2010/31/EU), air tightness of building envelopes in order to provide high thermal resistance leads to large moisture loads in building interiors. Among other factors, a high level of relative humidity has negative effect on the work efficiency and health of building inhabitants. A detailed insight into building materials behavior during cyclic moisture loading was accessed within this study. The moisture buffering values of three interior plasters were investigated in order to describe influence of plasters on moderation of indoor environment. Particular materials were loaded according to the NORDTEST protocol by 8/16 h loading schema at 70/30% RH. Here, the excellent moisture buffer classification was obtained for lightweight perlite plaster (PT) with the highest total open porosity. However, contrary to the higher total open porosity of renovation plaster (PS), the core plaster (CP) achieved higher moisture buffer capacity than PS. This discrepancy refers to the influence of the pore size distribution which is, besides the total open porosity, essential for a detailed characterization of moisture buffering potential of building materials. Based on the results of Mercury intrusion porosimetry, a correlation between pore size distribution and moisture buffer value was revealed